2010
DOI: 10.3233/ch-2010-1284
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte deformability in macrocytosis determined by means of ektacytometry techniques

Abstract: There is little information regarding the behaviour of red blood cell deformability in macrocytosis. We have determined in 114 patients with macrocytosis (MCV > 97 fL) and in 115 age and sex-matched subjects with normocytosis (VCM < 97 fL) erythrocyte deformability by means of ektacytometric techniques (Rheodyn SSD) measuring the erythrocyte elongation index (EEI) at 12, 30 and 60 Pa. Patients with macrocytosis showed statistically higher EEI at all the shear stresses tested when compared with controls (p < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…RBC are of pivotal importance in the human energy dynamic, and, it is known that they need to deform themselves to travel through capillaries for effective oxygen transportation. RBC deformability has been shown to be affected by ALT [34], AST [35], CRP [36], and 25-OH vitamin D levels [37]. Interestingly, recently, RBC deformability has been found to be impaired also in patients with chronic fatigue syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…RBC are of pivotal importance in the human energy dynamic, and, it is known that they need to deform themselves to travel through capillaries for effective oxygen transportation. RBC deformability has been shown to be affected by ALT [34], AST [35], CRP [36], and 25-OH vitamin D levels [37]. Interestingly, recently, RBC deformability has been found to be impaired also in patients with chronic fatigue syndrome [38].…”
Section: Discussionmentioning
confidence: 99%
“…In a similar way, the large red blood cell size in a macrocytosis patient may also disrupt the cochlea's microvascular supply. Macrocytic red blood cells have an increased surface area to volume ratio and are more easily deformed than normal cells (mean corpuscular volume < 100 fl) 8 . Pathological red blood cell deformability has been linked with sudden SNHL, 9 although the current understanding is that a reduction in red blood cell deformability leads to deterioration of blood flow through the labyrinthine branch of the posterior inferior cerebellar artery which supplies the cochlea.…”
Section: Discussionmentioning
confidence: 99%
“…The BMI of diabetic and reference group demonstrates obesity ( • ▶ Table 1 ). Vaya et al found a decrease of RCD in obese patients [ 35 ] . Despite of the fact that diabetes subjects lost weight over the 3 months training period the RCD tend to decrease.…”
mentioning
confidence: 95%